Innovative Factors Influencing the Decision to Stay at 3-Star Hotels in Phuket Province among Generation Y Tourists - Kayem , Vitsaroot; Keawnuch, Kanokkarn (Journal of International Studies, Prince of Songkla University, 2025)
This research aims to study the innovative factors influencing the decision-making process of staying at 3-star hotels in Phuket province among Generation Y tourists. It is quantitative research utilizing a questionnaire as a data collection tool from Thai tourists aged between 26 - 43 years who have previously traveled to Phuket province and stayed at 3-star hotels there. The sample size comprises 400 individuals. Data analysis involves frequency, percentage, mean, standard deviation, Pearson correlation analysis, and multiple regression analysis. The findings indicate that innovation factors consist of product innovation (β = 0.703, p < 0.01) and process innovation (β = 0.289, p < 0.01), which positively correlate with the decision-making process of staying at 3-star hotels in Phuket province among Generation Y tourists, with statistical significance at the 0.05 level.